Liquid Chromatography for Analysis of Metformin in Myrmeleon sp. - Afidatul Muadifah; Hermin Sulistyarti; Sasangka Prasetyawan (Chemistry Department, The University of Brawijaya, 2017)
Myrmeleon sp is a typical of insect larva which has been used in Indonesia for diabetes treatment. However, there is no sufficient scientific report explaining the bioactive compounds in this insect. Based on our preliminary research, this insect contained metformin, i.e. one of bioactive compounds for the treatment of type-2 diabetes. Therefore, this study is focused on the development of separation technique using high performance liquid chromatography (HPLC) on a reverse phase C-18 column with UV detection to identify and quantify metformin in methanol extract of Myrmeleon sp. Several parameters of HPLC method were optimized with respect to high resolution of separation and accurate determination of metformin. Satisfied separation was obtained under gradient elution mode using aqueous methanol mobile phase varied from 50-90 % of methanol with flow rate of 0.5 mL/min and detection wavelength of 233 nm. The method performed total separation for all compounds in less than 11 minutes. Spiking technique was chosen for metformin identification and quantitation. Metformin in extract Myrmeleon sp was eluted at retention time (tR) of 4.095 minutes, similarly with retention time of standard metformin of 4.092 minutes. The quantity of metformin in Myrmeleon sp can be simply determined by comparing the additional area of standard metformin with area of metformin from extract Myrmeleon sp. The results confirmed that methanol extract of Myrmeleon sp contained anti-diabetes compound of metformin of 0.58 mg/g Myrmeleon sp larvae with acceptable coefficient variation of 5.56 %.